2017
DOI: 10.1115/1.4037932
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Distinct Tendons From Elastin Haploinsufficient Mice Exhibit Mild Stiffening and Tendon-Specific Structural Alteration

Abstract: Elastic fibers are present in low quantities in tendon, where they are located both within fascicles near tenocytes and more broadly in the interfascicular matrix (IFM). While elastic fibers have long been known to be significant in the mechanics of elastin-rich tissue (i.e., vasculature, skin, lungs), recent studies have suggested a mechanical role for elastic fibers in tendons that is dependent on specific tendon function. However, the exact contribution of elastin to properties of different types of tendons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 64 publications
2
31
1
Order By: Relevance
“…145,146 Surprisingly, elastin-deficient tendons showed no alterations in biomechanical properties, with the exception of a slight increase in linear stiffness. 145 FBN1 and FBN2 were found in bovine flexor tendon and in canine flexor digitorum profundus tendon where FBN2 was localized in the PCM of the central tenocytes, while FBN1 localized to the PCM of the peripheral tenocyte layers. 143,147 The PCM around the tenocytes is rich in FBN2, which co-localized with versican, where it forms a sturdy ECM that allows for the proteolytic and mechanical isolation of intact tenocyte arrays.…”
Section: Fibrillins and Elastinmentioning
confidence: 93%
See 2 more Smart Citations
“…145,146 Surprisingly, elastin-deficient tendons showed no alterations in biomechanical properties, with the exception of a slight increase in linear stiffness. 145 FBN1 and FBN2 were found in bovine flexor tendon and in canine flexor digitorum profundus tendon where FBN2 was localized in the PCM of the central tenocytes, while FBN1 localized to the PCM of the peripheral tenocyte layers. 143,147 The PCM around the tenocytes is rich in FBN2, which co-localized with versican, where it forms a sturdy ECM that allows for the proteolytic and mechanical isolation of intact tenocyte arrays.…”
Section: Fibrillins and Elastinmentioning
confidence: 93%
“…Elastin haploinsufficiency in mice resulted in larger collagen fibrils in the Achilles tendon but not in the supraspinatus tendon . Surprisingly, elastin‐deficient tendons showed no alterations in biomechanical properties, with the exception of a slight increase in linear stiffness . FBN1 and FBN2 were found in bovine flexor tendon and in canine flexor digitorum profundus tendon where FBN2 was localized in the PCM of the central tenocytes, while FBN1 localized to the PCM of the peripheral tenocyte layers .…”
Section: The Pcm Of Tendon‐resident Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,[23][24][25][26] 3 | CONTENT AND DISTRIBUTION Excluding the elastin-rich spinal ligaments such as the nuchal ligament and ligamentum flavum, elastin content in tendon and ligament has been reported to range from as low as 0.25% to as high as 10% of the tissue's dry weight, with various reports of intermediate values. [27][28][29] Much of the variability in elastin content can be attributed to tissue specialization in order to accomplish specific functional requirements.…”
Section: Assembly and Developmentmentioning
confidence: 99%
“…Previous studies focussed on elucidating the contribution of elastin to tendon mechanics have identified alterations in failure stress and strain [15], stiffness [16] and shear response [17] as a result of elastin depletion, utilising either heterozygous knockout models or enzymatic digestion of elastin. However, to the authors' knowledge, no studies have investigated the effect of elastin depletion in energy storing tendons, or directly determined the effect of elastin depletion on IFM mechanics.…”
Section: Introductionmentioning
confidence: 99%